The Entanglement Generation in P T -Symmetric Optical Quadrimer System - Joanna K. Kalaga (Symmetry, 2019)
We discuss a model consisting of four single-mode cavities with gain and loss energy in the first and last modes. The cavities are coupled to each other by linear interaction and form a chain. Such a system is described by a non-Hermitian Hamiltonian which, under some conditions, becomes <semantics> P T </semantics> -symmetric. We identify the phase-transition point and study the possibility of generation bipartite entanglement (entanglement between all pairs of cavities) in the system.